The following extracts from the votes and proceedings of the American Continental Congress, we are induced to publish thus early purely to ease the impatience of the public : Association, &c. . (LLMC-digital (Series), 1774)
"An agreement between the twelve colonies not to trade with England, drafted by Thomas Cushing, Isaac Low, Thomas Mifflin, Richard Henry Lee, and Thomas Johnson, Jun."-- Ford, Some materials for a bibliography of the official publications of the Continental Congress, 1888, page 3.